2004
DOI: 10.1086/379887
|View full text |Cite
|
Sign up to set email alerts
|

Arp 299: A Second Merging System with Two Active Nuclei?

Abstract: Recent BeppoSAX observations of Arp 299, a powerful far-IR merging starburst system composed of IC 694 and NGC 3690, clearly unveiled for the first time in this system the presence of a strongly absorbed AGN. However, at the spatial resolution of the BeppoSAX instruments the system was not resolved. Here we present the analysis of archival Chandra and XMM-Newton observations, that allow us to disentangle the X-ray emission of the two galaxies. The detection of hard X-ray emission and strong Fe lines in both th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
168
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(181 citation statements)
references
References 24 publications
13
168
0
Order By: Relevance
“…Fe K features are found at 6.4 keV (line emission from cold Fe) and/or at higher energies (Fe xxv or Fe xxvi). The detection of these Fe K lines have been reported previously, based on XMM-Newton, ASCA, and Chandra observations (Imanishi et al 2003;Xia et al 2002;Armus et al 2009;Komossa et al 2003;Della ceca et al 2002;Ballo et al 2004;Clements et al 2002;Iwasawa & Comastri 1998;Turner & Kraemer 2003;Braito et al 2004). One addition is F17207-0014 for which a possible highionization Fe K line is detected (2σ) for the first time.…”
Section: Prominent Emission Linessupporting
confidence: 68%
See 2 more Smart Citations
“…Fe K features are found at 6.4 keV (line emission from cold Fe) and/or at higher energies (Fe xxv or Fe xxvi). The detection of these Fe K lines have been reported previously, based on XMM-Newton, ASCA, and Chandra observations (Imanishi et al 2003;Xia et al 2002;Armus et al 2009;Komossa et al 2003;Della ceca et al 2002;Ballo et al 2004;Clements et al 2002;Iwasawa & Comastri 1998;Turner & Kraemer 2003;Braito et al 2004). One addition is F17207-0014 for which a possible highionization Fe K line is detected (2σ) for the first time.…”
Section: Prominent Emission Linessupporting
confidence: 68%
“…A subsequent XMM-Newton observation resolved the two nuclei and found that the spectra of both nuclei show Fe lines but at different energies -at 6.4 keV in NGC 3690 W and at 6.7 keV in NGC 3690 E (Ballo et al 2004). The Chandra data alone provide detection of these lines at the 2σ level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sargent & Scoville 1991;Lonsdale et al 1992). From a comparison between the X-ray luminosity of A and B1, Ballo et al (2004) deduce that both IC 694 and NGC 3690 host AGN activity. According to them, such X-ray intensity could not be accounted for by star formation alone.…”
Section: Ic 694mentioning
confidence: 88%
“…Direct X-ray imaging of active nuclei have revealed several SMBH binaries at separations of ∼3 kpc (Komossa et al 2003;Ballo et al 2004;Bianchi et al 2008;Civano et al 2012), 400 pc (Paggi et al 2013), and 150 pc (Fabbiano et al 2011). Additional evidence comes in the form of a radio galaxy with a double core with a projected separation of 10 pc (Rodriguez et al 2006), and several other observations of radio galaxies, such as the wiggled shape of jets indicating precession (Roos et al 1993), the X-shaped morphologies of radio lobes (Merritt and Ekers 2002;Liu 2004), the interruption and recurrence of activity in double-double radio galaxies (Schoenmakers et al 2000;Liu et al 2003), and the elliptical motion of the unresolved core of 3C66B (Sudou et al 2003), which have all been interpreted as indirect evidence for SMBH binaries down to subparsec scales.…”
Section: Circumbinary Smbh Disksmentioning
confidence: 99%